Plastic Ingestion in Sardines (Sardinops sagax) From Frenchman Bay, Western Australia, Highlights a Problem in a Ubiquitous Fish - Crutchett, Thomas; Paterson, Harriet; Ford, Benjamin M.; Speldewinde, Peter (Frontiers in Marine Science, 2020)
The ingestion of plastic debris has been studied in many marine fish species, although comparisons between species can be difficult due to factors thought to influence ingestion rates, such as habitat preference, feeding behaviours and trophic level. Sardines are found internationally in many coastal environments and represent a potential sentinel species for monitoring and comparing marine plastic exposure rates. We conducted a pilot study, examining the rate of plastic ingestion in 27 commercially caught sardines (Sardinops sagax) from a low populated coastal region of Western Australia. A total of 251 potentially anthropogenic particles were extracted by chemical digestion of the gastrointestinal tract and classified visually. Fibres were the dominant type of material recovered (82.9%), with both yellow (39.8%) and black (32.7%) coloured particles commonly observed. A subset of 64 particles (25.5%), were subject to Fourier transform infrared (FTIR) spectroscopy to identify polymer composition. This chemical characterisation identified seven plastic items (polypropylene, nylon and polyethylene) and a variety of cellulose-based material that was further examined and classified as natural or semi-synthetic. The mean plastic ingestion rate was 0.3 ± 0.4 particles per fish, suggesting Western Australian sardines ingest relatively low concentrations of plastic when compared to international sardine populations examined using similar methodologies. Despite comparatively low concentrations, plastic and semi-synthetic material are still being ingested by sardines from a low populated coastal region demonstrating the ubiquitous nature of the marine debris problem.